Pengaruh Sistem Keuangan Desa (SISKEUDES), Sistem Pengendalian Internal Pemerintah, dan Kejelasan Sasaran Anggaran Terhadap Akuntabilitas Pengelolaan Dana Desa di Kabupaten Tapin - Indriaty Ermayani; Syaiful Hifni; Sarwani, Sarwani (Edunomics Journal, 2024)
This study aims to obtain empirical evidence regarding the influence of village financial systems, government internal control systems, and budget target clarity on the accountability of village fund management in Tapin Regency. This type of research is quantitative research. The data used in this study are primary data obtained using data collection techniques in the form of surveys using questionnaires. The sample in this study consisted of 80 respondents from village officials considered representative using convenience sampling techniques. The analysis technique used in this study is multiple linear regression analysis using software SPSS Version 21. The results of this study indicate that the village financial system, government internal control system, and budget target clarity positively influence the accountability of village fund management in Tapin Regency. These findings can serve as a reference for the government, particularly village administrations, to improve the accountability of village fund management. Consequently, village funds will function as intended, such as developing infrastructure, fostering community development, and empowering the community